Ética, educação e experiência formativa na temporalidade do presente - Ramos, Estéfani Dutra [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research has an objective think the subject of experience linked to education while degree´s space for the skill to experience. The importance of our research subject justify by present diagnoses about experience impoverishment consequent of advancement of technique and capitalism, what subject the man to new forms of dominate, blocking him to stablished a degree of sense with the tradition and,therefore, becoming him unable of tell and means his experiences. This diagnose tought range of education and culture makes prevailing at education a know-how in contraposition to know-expressing by experience of education. Our intention is reflect about a education that care impoverishment experience in a time marked by technological speech and a temporariness ruled by market logical. We´re doing this turning to the idea to an education poetical and the historical testimonial thinking for philosophers as Fernando Bárcena and Seligman-Silva in a intention of analysis the importance of a language of experience in a educational scene, as element for thinking in animation our experience in this space. Because of this, our trajectory is planned in na analysis of experience´s idea and “impoverishment of our experience” , tought by Walter Benjamin, mainly in essays “Experience and Poverty.”, The Storyteller...

Esta pesquisa tem como objetivo pensar o tema da experiência vinculado à educação enquanto espaço de formação para a aptidão à experiência. A importância do nosso tema de pesquisa justifica-se pelo atual diagnóstico acerca do empobrecimento da experiência resultante do avanço da técnica e do capitalismo, que submeteu o homem a novas formas de dominação impedindo-o de estabelecer um vínculo de sentido com a tradição e, portanto, tornando-o incapaz de narrar e significar suas experiências. Esse diagnóstico pensado no âmbito da educação e da cultura faz com que se predomine na formação um saber-fazer em contraposição ao saber-expressar próprio da experiência no cenário educativo. O nosso intuito é refletir acerca de uma educação que se atente para o empobrecimento da experiência numa época marcada pelos discursos tecnológicos e por uma temporalidade que é regida pela lógica do mercado. Fazemos isso recorrendo às noções de uma poética na educação e do testemunho histórico, pensados por filósofos como Fernando Bárcena e Seligmann-Silva no intuito de analisarmos a importância de uma linguagem da experiência no cenário educativo, como elemento para pensarmos a animação da nossa experiência nesse espaço...
Keywords: Educação; Experiencia; Ética; Conversação; Education